High-compactness industrial rubber glove and preparation method thereof
By using a double-layer structure design of nano-scale inorganic ore powder and styrene butadiene latex in rubber gloves, the problem of insufficient corrosion resistance of existing rubber gloves in harsh environments is solved, and the chemical resistance and density of gloves are significantly improved. Meets the protection needs in special areas.
Patent Information
- Application Number
- CN202411245938.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-03
AI Technical Summary
The existing rubber gloves have poor corrosion resistance and insufficient protection performance in harsh chemical environments such as acid and alkali, strong oxidation, and cannot meet the labor protection needs in special fields.
Designed with a double-layer structure, the outer layer contains nano-scale inorganic ore powder and styrene butadiene latex to form a wear-resistant and corrosion-resistant protective layer, and the inner layer also contains styrene butadiene latex to improve density and comfort, through specific The latex composition and process processing enhance the chemical resistance of the gloves.
It significantly improves the corrosion resistance and density of rubber gloves, delays the corrosion process of chemical media, enhances the protective performance of chemical reagents, and is simple and easy to mass production, avoiding the problem of easy coating falling off.
Smart Images

Figure CN119235070A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber gloves manufacturing, and in particular to a high-density industrial rubber glove and a preparation method thereof. Background Art
[0002] At present, natural rubber is a natural polymer compound with polyisoprene as the main component, 91%-94% of its components are polyisoprene, and the rest are non-rubber substances such as proteins, fatty acids, ash, and sugars. Natural rubber gloves have good strength, flexibility, elasticity and comfort, can isolate viruses and bacteria, and are widely used in various aspects such as medical protection, production and life. However, since the molecular structure of natural rubber is very similar to that of oil, it is easy for each other to enter each other's gaps. The chemical resistance of natural rubber gloves is poor and cannot be used in harsh chemical environments such as acid, alkali, and strong oxidation. With the increasing development of industry, the demand for corrosion-resistant, oil-resistant, and solvent-resistant polymer gloves has become increasingly greater. The existing polymer gloves are not very ideal in terms of air permeability or corrosion resistance. Their protective performance needs to be further improved and cannot meet the labor protection needs in special fields.
[0003] Nano-silicon dioxide particles have a very high specific surface area due to their extremely small particle size, making them more likely to undergo physical or chemical adsorption with other substances, forming a protective film on their surface, effectively adsorbing and blocking corrosive media, and greatly delaying the corrosion process. However, in daily necessities, nano-silicon dioxide is currently mostly applied as a coating on the surface of the product to achieve an anti-corrosion effect, but this process has the problem that the coating is easy to fall off and needs to be repeatedly applied regularly, affecting its anti-corrosion effect. Long-term use of coated corrosion-resistant gloves requires frequent replacement and is prone to causing the anti-corrosion effect to fail due to the shedding of the coating, causing harm to the staff. Therefore, it is of great significance to develop a high-density industrial rubber glove with outstanding anti-corrosion effect and long-lasting anti-corrosion time. Summary of the invention
[0004] The object of the present invention is to provide a high-density industrial rubber glove and a preparation method thereof, so as to solve the technical problems that the rubber gloves in the prior art have poor anti-corrosion effect and low density.
[0005] In order to solve the above technical problems, the present invention provides a high-density industrial rubber glove, wherein the rubber glove has a double-layer structure, including a corrosion-resistant layer and a comfortable wearing layer;
[0006] The corrosion-resistant layer is located on the outer surface of the rubber gloves and contains: by mass:
[0007] 70-80 parts of sulfurized carboxylated nitrile latex, 15-20 parts of styrene-butadiene latex, 3-8 parts of nano-grade inorganic mineral powder, 1-2 parts of aluminum oxide, 0.3-0.8 parts of polypropylene glycol, and 0.5-1 parts of amyl octanoate;
[0008] The nano-scale inorganic mineral powder is selected from nano-silicon dioxide, nano-calcium carbonate, nano-clay and nano-titanium oxide.
[0009] The nano-scale inorganic mineral powder usually has high purity and fine particle size, low surface defects and impurity content, and high hardness. It can form a protective layer of nano-scale inorganic mineral powder on the rubber surface, thereby achieving the effect of improving the wear resistance and corrosion resistance of rubber gloves; on the other hand, the nano-scale inorganic mineral powder also has a high specific surface area and can form a "maze effect" on corrosive liquids, thereby more effectively absorbing and blocking the invasion of corrosive media and delaying the corrosion process.
[0010] The comfortable wearing layer is located on the inner surface of the rubber gloves and contains: by mass:
[0011] 70-80 parts of sulfurized carboxylated nitrile latex, 15-25 parts of styrene-butadiene latex, 1.5-2 parts of zinc oxide, 0.3-0.8 parts of polypropylene glycol, and 0.5-1 parts of amyl octanoate.
[0012] Styrene butadiene latex is added to both the corrosion-resistant layer and the comfortable wearing layer. On the one hand, the polymer particles in the styrene butadiene latex can fill the pores of the material to improve the density of the inner and outer layers; on the other hand, the styrene butadiene latex can form a tighter three-dimensional network structure during the cross-linking and curing process, thereby improving the overall density and strength of the material.
[0013] Furthermore, the preparation method of the above-mentioned high-density industrial rubber gloves comprises the following steps:
[0014] Step 1, immersing the cleaned glove mold in a coagulant at 40-45°C, leaving it for 3-5 seconds, then taking it out and drying it at low temperature to obtain a glove mold with a coagulant coated on the surface;
[0015] Step 2, immersing the glove mold with the coagulant coated on the surface into the first mixed latex, leaving it at room temperature for 6-8 seconds, then taking it out and drying it at low temperature to obtain a glove mold with a corrosion-resistant layer attached thereto;
[0016] Step 3, immersing the glove mold with the corrosion-resistant layer attached to the surface into the second mixed latex, leaving it for 8-10 seconds, taking it out and drying it at 100-115° C. for 6-8 minutes to obtain a glove mold with a comfortable wearing layer and a corrosion-resistant layer attached thereto;
[0017] Step 4, immersing the glove mold with the comfortable wearing layer and the corrosion-resistant layer in hot water at 75-85° C. for 15-20 seconds, taking it out, drying it, immersing it in an isolation agent solution for 10 seconds, taking it out, drying it, and demoulding it to obtain the high-density industrial rubber gloves.
[0018] Furthermore, the composition of the coagulant in step 1 is as follows:
[0019] Every 1000 parts of the coagulant contains 100-150 parts of calcium nitrate, 20-30 parts of calcium stearate, 20-30 parts of cellulose solution, 0.6-1 part of wetting agent 324, 0.5-1 part of perglase O, and the balance is water.
[0020] Further, the preparation steps of the first mixed latex in step 2 are as follows:
[0021] Step A1, taking 70-80 parts of sulfurized carboxylated nitrile latex and mixing them thoroughly with 15-20 parts of styrene-butadiene latex to obtain a first reaction mixture;
[0022] Step A2, sequentially adding 3-8 parts of a nano-scale inorganic mineral powder suspension, 1-2 parts of an aluminum oxide dispersion, 0.3-0.8 parts of polypropylene glycol, and 0.5-1 parts of amyl octanoate to the first reaction mixture, and stirring for 1-2 hours to obtain the first mixed latex;
[0023] The above components are all calculated by mass.
[0024] Adding aluminum oxide as a filler to the first mixed latex can enhance the cohesive strength of the rubber, making it less likely to be damaged when subjected to external forces, and improves the adhesion between the rubber and other materials.
[0025] Preferably, the nano-scale inorganic mineral powder in step A2 is selected from nano-silicon dioxide, nano-calcium carbonate, nano-clay, and nano-titanium oxide.
[0026] Further, the preparation steps of the second mixed latex in step 3 are as follows:
[0027] Step B1, taking 70-80 parts of sulfurized carboxylated nitrile latex and mixing them thoroughly with 15-25 parts of styrene-butadiene latex to obtain a second reaction mixture;
[0028] Step B2, adding 1.5-2 parts of zinc oxide, 0.3-0.8 parts of polypropylene glycol, and 0.5-1 parts of amyl octanoate to the second reaction mixture in sequence, stirring evenly to obtain the second mixed latex;
[0029] The above components are all calculated by mass.
[0030] Further, the preparation steps of the vulcanized carboxyl nitrile latex are as follows:
[0031] Step C1, taking 88-95 parts of carboxylated nitrile latex, adding 1-2 parts of 5% potassium hydroxide, adjusting the pH to 9-10, and obtaining a third reaction mixture;
[0032] Step C2, adding 0.8-1.5 parts of an antioxidant, 0.6-1.5 parts of sulfur, 1.5-2 parts of zinc oxide, and 0.8-1.5 parts of an accelerator to the third reaction mixture in sequence, stirring evenly to obtain a fourth reaction mixture;
[0033] Step C3, vulcanizing the fourth reaction mixture at room temperature for 14-18 hours to obtain the vulcanized carboxylated nitrile latex;
[0034] The above components are all calculated by mass.
[0035] Preferably, the accelerator in step C2 is selected from zinc diethyldithiocarbamate and zinc ethylphenyldithiocarbamate.
[0036] By adopting the above technical solution, the present invention has the following beneficial effects:
[0037] The present invention provides a high-density industrial rubber glove and a preparation method thereof. The rubber glove is designed into an inner and outer double-layer structure, which is conducive to the inner and outer rubber layers to play different functions respectively. Nano inorganic mineral powder is creatively introduced into the outer rubber layer to enhance the chemical corrosion resistance and wear resistance of the latex system, and aluminum oxide is introduced to increase the adhesion between the latexes; styrene-butadiene latex is introduced into both the inner and outer double-layer latexes, which significantly increases the density of the system. The preparation method of the high-density industrial rubber glove provided by the present invention has a simple process and is easy to mass produce. In particular, the process of twice dipping in latex solves the problem that pinholes are easy to appear in thick gloves, resulting in unqualified products, and is worthy of wide promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 A schematic diagram of the structure of the high-density industrial rubber gloves provided by the present invention;
[0040] Figure 2 A process flow chart of the preparation of high-density industrial rubber gloves provided by the present invention;
[0041] Figure 3 A process flow chart for preparing the first mixed latex provided in Example 1;
[0042] Figure 4 This is a process flow chart for preparing the second mixed latex provided in Example 1. DETAILED DESCRIPTION
[0043] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] The present invention is further explained below in conjunction with specific implementation modes.
[0045] like Figure 1-Figure 2 As shown, the preparation method of the high-density industrial rubber gloves provided by the present invention comprises the following specific steps:
[0046] Step 1, adding 1-2 parts of 5% potassium hydroxide to 88-95 parts of carboxyl nitrile latex, adjusting the pH value to 9-10, and then sequentially adding 0.8-1.5 parts of an antioxidant, 0.6-1.5 parts of sulfur, 1.5-2 parts of zinc oxide, and 0.8-1.5 parts of an accelerator, stirring evenly, and vulcanizing at room temperature for 14-18 hours to obtain a vulcanized carboxyl nitrile latex;
[0047] Step 2, taking 70-80 parts of sulfurized carboxyl nitrile latex and mixing it with 15-20 parts of styrene butadiene latex; then adding 3-8 parts of nano-scale inorganic mineral powder suspension, 1-2 parts of aluminum oxide dispersion, 0.3-0.8 parts of polypropylene glycol, and 0.5-1 parts of amyl octanoate in sequence, stirring for 1-2 hours to obtain the first mixed latex for standby use;
[0048] Step 3, taking 70-80 parts of sulfurized carboxyl nitrile latex and mixing it with 15-25 parts of styrene-butadiene latex; adding 1.5-2 parts of zinc oxide, 0.3-0.8 parts of polypropylene glycol, and 0.5-1 parts of amyl octanoate in sequence, stirring evenly to obtain a second mixed latex for standby use;
[0049] Step 4, immersing the cleaned glove mold in a coagulant at 40-45° C., leaving it for 3-5 seconds, taking it out and drying it at low temperature to obtain a glove mold with a coagulant coated on the surface;
[0050] Step 5, immersing the glove mold coated with a coagulant in the first mixed latex obtained in step 2, leaving it at room temperature for 6-8 seconds, then taking it out and drying it at low temperature to obtain a glove mold with a corrosion-resistant layer attached thereto;
[0051] Step 6, immersing the glove mold with the corrosion-resistant layer in the second mixed latex obtained in step 3, taking it out after staying for 8-10 seconds, and drying it at 100-115° C. for 6-8 minutes;
[0052] Step 7, immersing the glove mold with the comfortable wearing layer and the corrosion-resistant layer attached which has not been completely dried in step 6 into hot water at 75-85°C for 15-20s; taking out the mold, drying it and immersing it in a release agent for 10s, then taking it out for drying and demolding, thereby obtaining a high-density industrial rubber glove.
[0053] Example 1
[0054] like Figure 3-Figure 4 As shown, high-density industrial rubber gloves are prepared according to the method provided by the present invention.
[0055] Step 1, add 1.5KG of 5% potassium hydroxide to 90KG of carboxyl nitrile latex, adjust the pH value to 9-10, then add 1.2KG of antioxidant KY-616, 0.8KG of sulfur, 1.6KG of zinc oxide, and 1KG of zinc diethyl dithiocarbamate as accelerators in sequence, stir evenly, and then vulcanize at room temperature for 16 hours to obtain vulcanized carboxyl nitrile latex;
[0056] Step 2, take 75 kg of sulfurized carboxyl nitrile latex and mix it thoroughly with 20 kg of styrene butadiene latex; then add 5 kg of nano-scale silica suspension ( 40%), 1.5KG of 30% aluminum oxide dispersion, 0.5KG of polypropylene glycol, 0.8KG of amyl octanoate, fully stirred for 1-2 hours to obtain the first mixed latex, which is set aside;
[0057] Step 3, take 75 kg of sulfurized carboxyl nitrile latex and fully mix it with 22.2 kg of styrene butadiene latex; add 1.7 kg of zinc oxide, 0.3 kg of polypropylene glycol, and 0.8 kg of amyl octanoate in sequence, stir evenly, and obtain a second mixed latex for standby use;
[0058] Step 4, immersing the cleaned glove mold in a coagulant at 45° C., leaving it for 4 seconds, taking it out and drying it at low temperature to obtain a glove mold with a coagulant coated on the surface;
[0059] Step 5, immersing the glove mold coated with a coagulant in the first mixed latex obtained in step 2, leaving it at room temperature for 7 seconds, then taking it out and drying it at low temperature to obtain a glove mold with a corrosion-resistant layer attached thereto;
[0060] Step 6, immersing the glove mold with the corrosion-resistant layer in the second mixed latex obtained in step 3, taking it out after staying for 9 seconds, and drying it at 110° C. for 7 minutes;
[0061] Step 7, immersing the glove mold with the comfortable wearing layer-corrosion-resistant layer attached which has not been completely dried in step 6 into 80° C. hot water for 18 seconds; taking out the mold, drying it, and immersing it in a release agent for 10 seconds, then taking it out, drying it, and demolding it to obtain a high-density industrial rubber glove.
[0062] The high-density industrial rubber gloves obtained in this example and commercially available pure nitrile gloves were tested for tolerance to the following six chemical reagents according to the test standard of EN374-2019+AC:2018. The test standards are shown in Table 1 and the results are shown in Table 2.
[0063] Table 1: Determination criteria for penetration level according to EN374-2019+AC:2018
[0064] Breakthrough time / min Penetration Level >10 1 >30 2 >60 3 >120 4 >240 5 >480 6
[0065] Table 2 Comparison of corrosion resistance of high-density industrial rubber gloves obtained in Example 1 and commercially available pure nitrile gloves
[0066]
[0067] It can be seen from Tables 1 and 2 that according to the preparation method provided by the present invention, the high-density industrial rubber gloves added with nano-inorganic mineral powder and styrene-butadiene latex during the preparation process have significantly enhanced penetration breakthrough time for 6 chemical reagents compared with commercially available pure nitrile gloves, and the penetration level reaches Level 6, which proves that the above ingredients have a significant positive effect on the corrosion resistance of rubber.
[0068] Example 2
[0069] Step 1, add 1KG of 5% potassium hydroxide to 88KG of carboxyl nitrile latex, adjust the pH value to 9-10, then add 1KG of antioxidant KY-616, 0.6KG of sulfur, 1.5KG of zinc oxide, and 0.8KG of zinc diethyl dithiocarbamate as accelerators in sequence, stir evenly, and then vulcanize at room temperature for 18 hours to obtain vulcanized carboxyl nitrile latex;
[0070] Step 2, take 80 kg of sulfurized carboxyl nitrile latex and mix it thoroughly with 15 kg of styrene butadiene latex; then add 3 kg of nano-scale inorganic mineral powder suspension ( 40%), 1 kg of 30% aluminum oxide dispersion, 0.3 kg of polypropylene glycol, and 0.5 kg of amyl octanoate, and stirred for 2 hours to obtain the first mixed latex for standby use;
[0071] Step 3, take 80 kg of sulfurized carboxyl nitrile latex and fully mix it with 17 kg of styrene butadiene latex; add 1.5 kg of zinc oxide, 0.3 kg of polypropylene glycol, and 0.5 kg of amyl octanoate in sequence, stir evenly, and obtain a second mixed latex for standby use;
[0072] Step 4, immersing the cleaned glove mold in a coagulant at 40° C., leaving it for 5 seconds, taking it out and drying it at low temperature to obtain a glove mold with a coagulant coated on the surface;
[0073] Step 5, immersing the glove mold coated with a coagulant in the first mixed latex obtained in step 2, leaving it at room temperature for 6 seconds, then taking it out and drying it at low temperature to obtain a glove mold with a corrosion-resistant layer attached thereto;
[0074] Step 6, immersing the glove mold with the corrosion-resistant layer in the second mixed latex obtained in step 3, taking it out after staying for 8 seconds, and drying it at 100° C. for 8 minutes;
[0075] Step 7, immersing the glove mold with the comfortable wearing layer-corrosion-resistant layer attached which has not been completely dried in step 6 into hot water at 75°C for 15 seconds; taking out the mold, drying it, and immersing it in a release agent for 10 seconds, then taking it out, drying it, and demolding it to obtain a high-density industrial rubber glove.
[0076] Example 3
[0077] This example demonstrates the effect of styrene-butadiene latex on the corrosion resistance and compactness of high-density industrial rubber gloves.
[0078] Step 1, add 2KG of 5% potassium hydroxide to 95KG of carboxyl nitrile latex, adjust the pH value to 9-10, then add 1.5KG of antioxidant KY-616, 1.5KG of sulfur, 2KG of zinc oxide, and 1.5KG of zinc diethyl dithiocarbamate as accelerators in sequence, stir evenly, and then vulcanize at room temperature for 16 hours to obtain vulcanized carboxyl nitrile latex;
[0079] Step 2, take 70 kg of sulfurized carboxyl nitrile latex, and then add 8 kg of nano-scale silica suspension ( 40%), 2 kg of 30% aluminum oxide dispersion, 0.8 kg of polypropylene glycol, and 1 kg of amyl octanoate, and fully stirred for 1-2 hours to obtain the first mixed latex for standby use;
[0080] Step 3, take 70 kg of sulfurized carboxyl nitrile latex, add 2 kg of zinc oxide, 0.8 kg of polypropylene glycol, and 1 kg of amyl octanoate in sequence, stir evenly to obtain a second mixed latex, and set aside;
[0081] Step 4, immersing the cleaned glove mold in a coagulant at 45° C., leaving it for 3 seconds, taking it out and drying it at low temperature to obtain a glove mold with a coagulant coated on the surface;
[0082] Step 5, immersing the glove mold coated with a coagulant in the first mixed latex obtained in step 2, leaving it at room temperature for 8 seconds, then taking it out and drying it at low temperature to obtain a glove mold with a corrosion-resistant layer attached thereto;
[0083] Step 6, immersing the glove mold with the corrosion-resistant layer in the second mixed latex obtained in step 3, taking it out after staying for 10 seconds, and drying it at 115° C. for 6 minutes;
[0084] Step 7, immersing the glove mold with the comfortable wearing layer-corrosion-resistant layer attached which has not been completely dried in step 6 into hot water at 85°C for 20 seconds; taking out the mold, drying it, and immersing it in a release agent for 10 seconds, then taking it out, drying it, and demolding it to obtain a high-density industrial rubber glove.
[0085] Table 3 Comparison of corrosion resistance of high-density industrial rubber gloves obtained in Example 1 and Example 3
[0086]
[0087]
[0088] As can be seen from Table 3, in the glove sample of Example 3, no styrene-butadiene latex is added to the outer corrosion-resistant layer and the inner comfortable wearing layer, and the pores formed during the cross-linking and curing process of the rubber cannot be effectively filled, making it easier for chemical reagents to corrode the rubber itself, resulting in a decrease in the corrosion resistance of the rubber gloves. However, it is still significantly better than the corrosion resistance of commercially available pure nitrile gloves.
[0089] Example 4
[0090] This example verifies the effect of adding nano inorganic mineral powder on the corrosion resistance of rubber gloves.
[0091] The preparation parameters of this example are basically the same as those of Example 1, except that in step 2, nano-calcium carbonate and nano-titanium oxide are used as nano-inorganic mineral powders, both in an amount of 5 kg, and the obtained glove samples are marked as Example 4-1 and Example 4-2, respectively. The corrosion resistance of the two glove samples obtained in this example is tested according to the test standard of EN374-2019+AC:2018, and the results are shown in Table 4:
[0092] Table 4 Comparison of corrosion resistance of the glove samples of Examples 4-1 and 4-2 and the glove sample of Example 1
[0093]
[0094] As can be seen from Table 4, the glove sample of Example 4-1 added with nano-calcium carbonate has a slightly lower corrosion resistance than the glove sample of Example 1 because the specific surface area of nano-calcium carbonate is smaller than that of nano-silicon dioxide and the maze effect is reduced. The glove sample of Example 4-2 added with nano-titanium oxide has the same significant chemical reagent corrosion resistance as the glove sample of Example 1. Considering the production cost and industrialization requirements, the nano-inorganic mineral powder selected in the preparation method of the high-density industrial rubber gloves provided by the present invention is preferably a nano-silicon dioxide suspension.
[0095] In summary, the corrosion resistance test results of the samples obtained in various embodiments provided by the present invention are shown in Table 5 below:
[0096] Table 5 Corrosion resistance test of glove samples obtained in various embodiments provided by the present invention
[0097]
[0098] As can be seen from Table 5, the corrosion resistance of the glove samples obtained in each embodiment according to the preparation method provided by the present invention is significantly better than that of the pure nitrile gloves on the market. The two glove samples obtained in Example 4 both show that the addition of nano inorganic mineral powder can form a dense protective layer composed of inorganic mineral powder on the rubber surface to prevent chemical reagents from contacting the rubber, and because the nano inorganic mineral powder has a high specific surface area, it can form a maze effect, greatly delaying the erosion process of chemical reagents on the rubber. Therefore, the type and amount of nano inorganic mineral powder added play a very important role in the corrosion resistance of rubber gloves. The test results of the glove samples obtained in Example 3 show that the appropriate addition of styrene butadiene latex can fill the pores formed by the rubber during the cross-linking and curing process, significantly increase the compactness of the rubber, and thus delay the corrosion of chemical reagents.
[0099] The preparation method of the high-density industrial rubber gloves provided by the present invention increases the protection of rubber by introducing nano inorganic mineral powder and styrene butadiene latex, significantly delaying the corrosion process of chemical reagents; at the same time, the rubber gloves are designed into an inner and outer double-layer structure, which ensures that the outer gloves have a nano inorganic mineral powder protective layer on the one hand, giving full play to its corrosion resistance, and on the other hand, the inner layer is more comfortable and suitable for wearing, avoiding the harm to the human body caused by the rough arrangement of nano inorganic mineral powder during work. The preparation method of the high-density industrial rubber gloves provided by the present invention has a simple process and is easy to mass produce. In particular, the process of twice dipping in latex solves the technical problem that pinholes are easy to appear in thick gloves, resulting in unqualified products, and is worthy of wide promotion.
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-density industrial rubber glove, characterized in that: The rubber gloves have a corrosion-resistant layer and a comfortable wearing layer; The corrosion-resistant layer is located on the outer surface of the rubber gloves and contains sulfurized carboxylated nitrile latex, styrene-butadiene latex, polypropylene glycol, amyl octanoate, nano-scale inorganic mineral powder, and aluminum oxide; The comfortable wearing layer is located on the inner surface of the rubber gloves and contains sulfurized carboxylated nitrile latex, styrene-butadiene latex, polypropylene glycol, amyl octanoate and zinc oxide.
2. The rubber glove according to claim 1, characterized in that: The content of each component in the corrosion-resistant layer is as follows: 70-80 parts of sulfurized carboxyl nitrile latex, 15-20 parts of styrene-butadiene latex, 3-8 parts of nano-grade inorganic mineral powder, 1-2 parts of aluminum oxide, 0.3-0.8 parts of polypropylene glycol, and 0.5-1 parts of amyl octanoate.
3. The rubber glove according to claim 1 or 2, characterized in that: The nano-scale inorganic mineral powder is selected from nano-silicon dioxide, nano-calcium carbonate, nano-clay and nano-titanium oxide.
4. The rubber glove according to claim 1, characterized in that: The content of each component in the comfortable wearing layer is as follows: 70-80 parts of sulfurized carboxylated nitrile latex, 15-25 parts of styrene-butadiene latex, 1.5-2 parts of zinc oxide, 0.3-0.8 parts of polypropylene glycol, and 0.5-1 parts of amyl octanoate.
5. A method for preparing rubber gloves according to claim 1, characterized in that: Here are the steps: Step 1, immersing the cleaned glove mold in a coagulant at 40-45° C., leaving it for 3-5 seconds, taking it out and drying it at low temperature to obtain a glove mold with a coagulant coated on the surface; Step 2, immersing the glove mold with the coagulant coated on the surface into the first mixed latex, leaving it at room temperature for 6-8 seconds, then taking it out and drying it at low temperature to obtain a glove mold with a corrosion-resistant layer attached thereto; Step 3, immersing the glove mold with the corrosion-resistant layer attached to the surface into the second mixed latex, taking it out after staying for 8-10 seconds, and drying it at 100-115° C. for 6-8 minutes to obtain a glove mold with a comfortable wearing layer and a corrosion-resistant layer attached; Step 4, immersing the glove mold with the comfortable wearing layer and the corrosion-resistant layer in hot water at 75-85° C. for 15-20 seconds, taking it out, drying it, immersing it in an isolation agent solution for 10 seconds, taking it out, drying it, and demoulding it to obtain the high-density industrial rubber gloves.
6. The preparation method according to claim 5, characterized in that: The composition of the coagulant in step 1 is as follows: Every 1000 parts of the coagulant contains 100-150 parts of calcium nitrate, 20-30 parts of calcium stearate, 20-30 parts of cellulose solution, 0.6-1 part of wetting agent 324, 0.5-1 part of perglase O, and the balance is water.
7. The preparation method according to claim 5, characterized in that: The preparation steps of the first mixed latex in step 2 are as follows: Step A1, taking 70-80 parts of sulfurized carboxylated nitrile latex and mixing them thoroughly with 15-20 parts of styrene-butadiene latex to obtain a first reaction mixture; Step A2, sequentially adding 3-8 parts of a nano-scale inorganic mineral powder suspension, 1-2 parts of an aluminum oxide dispersion, 0.3-0.8 parts of polypropylene glycol, and 0.5-1 parts of amyl octanoate to the first reaction mixture, and stirring for 1-2 hours to obtain the first mixed latex; The above components are all calculated by mass.
8. The preparation method according to claim 5, characterized in that: The preparation steps of the second mixed latex in step 3 are as follows: Step B1, taking 70-80 parts of sulfurized carboxylated nitrile latex and mixing them thoroughly with 15-25 parts of styrene-butadiene latex to obtain a second reaction mixture; Step B2, adding 1.5-2 parts of zinc oxide, 0.3-0.8 parts of polypropylene glycol, and 0.5-1 parts of amyl octanoate to the second reaction mixture in sequence, stirring evenly to obtain the second mixed latex; The above components are all calculated by mass.
9. The preparation method according to claim 7 or 8, characterized in that: The preparation steps of the vulcanized carboxyl nitrile latex are as follows: Step C1, taking 88-95 parts of carboxylated nitrile latex, adding 1-2 parts of 5% potassium hydroxide, adjusting the pH value to 9-10, and obtaining a third reaction mixture; Step C2, adding 0.8-1.5 parts of an antioxidant, 0.6-1.5 parts of sulfur, 1.5-2 parts of zinc oxide, and 0.8-1.5 parts of an accelerator to the third reaction mixture in sequence, stirring evenly to obtain a fourth reaction mixture; Step C3, vulcanizing the fourth reaction mixture at room temperature for 14-18 hours to obtain the vulcanized carboxylated nitrile latex; The above components are all calculated by mass.
10. The preparation method according to claim 9, characterized in that: The accelerator described in step C2 is selected from zinc diethyldithiocarbamate and zinc ethylphenyldithiocarbamate.
